[Accepted, unedited version] The dark side of drug repurposing, from clinical trial challenges to antimicrobial resistance: analysis based on three major fields - Iyad Y. Natsheh; Majd M. Alsaleh; Ahmad K. Alkhawaldeh; Duaa K. Albadawi; Maisa' M. Darwish; Mohammed Jamal A. Shammout (AboutScience Srl, 2024)
Drug repurposing is a strategic endeavor that entails the identification of novel therapeutic applications for pharmaceuticals that are already available in the market. Despite the advantageous nature of implement- ing this particular strategy owing to its cost-effectiveness and efficiency in reducing the time required for the drug discovery process, it is essential to bear in mind that there are various factors that must be meticulously considered and taken into account. Up to this point, there has been a noticeable absence of comprehensive analyses that shed light on the limitations of repurposing drugs. The primary aim of this review is to con- duct a thorough illustration of the various challenges that arise when contemplating drug repurposing from a clinical perspective in three major fields cardiovascular, cancer and diabetes and to further underscore the potential risks associated with the emergence of antimicrobial resistance when employing repurposed antibiotics for the treatment of noninfectious and infectious diseases. The process of developing repurposed medications necessitates the application of creativity and innovation in designing the development program, as the body of evidence may differ for each specific case. In order to effectively repurpose drugs, it is crucial to consider the clinical implications and potential drawbacks that may arise during this process. By com- prehensively analyzing these challenges, we can attain a deeper comprehension of the intricacies involved in drug repurposing, which will ultimately lead to the development of more efficacious and safe therapeutic approaches.